2016
DOI: 10.1007/s00299-016-1995-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis reveals the positive effect of exogenous spermidine on photosynthesis and salinity tolerance in cucumber seedlings

Abstract: Our results based on proteomics data and physiological alterations proposed the putative mechanism of exogenous Spd enhanced salinity tolerance in cucumber seedlings. Current studies showed that exogenous spermidine (Spd) could alleviate harmful effects of salinity. It is important to increase our understanding of the beneficial physiological responses of exogenous Spd treatment, and to determine the molecular responses underlying these responses. Here, we combined a physiological analysis with iTRAQ-based com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 68 publications
2
24
0
Order By: Relevance
“…These results clearly suggested that the cucumber seedlings with Spd attributed to significant improvement in growth status under high salinity. The findings were consistent with existing research results [16,19,22].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These results clearly suggested that the cucumber seedlings with Spd attributed to significant improvement in growth status under high salinity. The findings were consistent with existing research results [16,19,22].…”
Section: Discussionsupporting
confidence: 93%
“…For instance, PAs can protect negatively charged macromolecules, such as DNA, RNA, and certain proteins [14]. Moreover, recent studies have shown that PAs have diverse functions and roles in response to plant stress [15,16]. For instance, PAs can act as direct hydroxyl radical scavenging and influence antioxidant activity at molecular and gene expression level.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations